2023
DOI: 10.1136/jitc-2022-006628
|View full text |Cite
|
Sign up to set email alerts
|

Vaccinating against cancer: getting to prime time

Abstract: Immunotherapies, such as immune checkpoint inhibitors, cellular therapies, and T-cell engagers, have fundamentally changed our approach to treating cancer. However, successes with cancer vaccines have been more difficult to realize. While vaccines against specific viruses have been widely adopted to prevent the development of cancer, only two vaccines can improve survival in advanced disease: sipuleucel-T and talimogene laherparepvec. These represent the two approaches that have the most traction: vaccinating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 119 publications
(102 reference statements)
0
4
0
Order By: Relevance
“…Unlike most other immunotherapies, cancer vaccines typically have minimal side effects, as they rely on the selection of highly immunogenic tumor antigens that are only expressed by cancer cells. Tumor antigens can be classified as tumor-associated antigens (TAAs) or tumor-specific antigens (TSAs) [ 10 , 17 ]. TAAs are preferentially overexpressed on tumor cells but can be present in healthy cells, or they may be cancer/testis antigens that are only expressed by tumor cells and adult reproductive tissues.…”
Section: Immunotherapy and Therapeutic Cancer Vaccinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike most other immunotherapies, cancer vaccines typically have minimal side effects, as they rely on the selection of highly immunogenic tumor antigens that are only expressed by cancer cells. Tumor antigens can be classified as tumor-associated antigens (TAAs) or tumor-specific antigens (TSAs) [ 10 , 17 ]. TAAs are preferentially overexpressed on tumor cells but can be present in healthy cells, or they may be cancer/testis antigens that are only expressed by tumor cells and adult reproductive tissues.…”
Section: Immunotherapy and Therapeutic Cancer Vaccinesmentioning
confidence: 99%
“…TAAs are preferentially overexpressed on tumor cells but can be present in healthy cells, or they may be cancer/testis antigens that are only expressed by tumor cells and adult reproductive tissues. TSAs, conversely, are de novo epitopes expressed by oncoviruses and shared or individual-specific neoantigens encoded by somatic mutations [ 17 ]. Compared to cancer vaccines that use TAAs or TSAs to induce tumor-reactive T cells, whole tumor-derived approaches have the benefit of being truly antigen-inclusive.…”
Section: Immunotherapy and Therapeutic Cancer Vaccinesmentioning
confidence: 99%
“… 21 , 37 , 38 , 39 , 40 , 41 , 42 , 43 To date, therapeutic mAbs encoded by mRNA LNPs have been used and reported in numerous preclinical and clinical studies. 16 , 18 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 An mRNA LNP-based therapeutic mAb expression system has several potential advantages over recombinant mAbs for the treatment of patients. The variation of recombinant products produced in different cell systems can be diminished.…”
Section: Discussionmentioning
confidence: 99%
“…The oldest studies selected in the present review present data on the clinical testing the EVs in the field of cancer immunotherapy; this approach, generally aimed at strengthening or inducing host antitumor immune response, is now an established therapeutic option adding to the traditional chemo‐ and radiotherapy to treat both haematological and solid malignancies (Esfahani et al., 2020 ). In particular, the adoptive transfer of autologous dendritic cells (DC) pulsed with tumour peptides to drive anti‐tumour specific T cell responses, approved by the Food and Drug Administration (FDA) in 2010, was demonstrated to prolong survival of metastatic castration‐resistant prostate cancer patients (Chang et al., 2023 ; Kantoff et al., 2010 ) The possible development of an alternative vaccination strategy, based on tumour antigen‐presenting EVs of DC origin, was suggested by a milestone paper published at the end of last century which demonstrated that the EVs released by cancer peptide‐pulsed DCs could prime cytotoxic T cells and induce the rejection of established tumours in mice (Zitvogel et al., 1998 ). EVs were hypothesized to have the advantage of expressing high levels of antigens, in combination with costimulatory molecules; as a matter of fact, DC‐derived EVs were characterized at the molecular level and the procedures for their purification and storage optimized (Lamparski et al., 2002 ; Théry et al., 2001 ).…”
Section: Cancer Immunotherapymentioning
confidence: 99%